2017
DOI: 10.1038/s41598-017-17897-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics reveals novel blood plasma biomarkers associated to the BRCA1-mutated phenotype of human breast cancer

Abstract: Hereditary breast and ovarian cancer syndrome (HBOC) is partly due to the presence of mutations in the BRCA genes. Triple-negative (TN) breast cancer (BC) shares histological characteristics with germline BRCA1 mutation-associated tumours. We have investigated the metabolic profiles of human breast cancer (BC) cell lines carrying BRCA1 pathogenic mutations by non-targeted liquid chromatography coupled to mass spectrometry technology. Based on our in vitro results, we performed a targeted metabolomic analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 51 publications
1
30
0
1
Order By: Relevance
“…Breast cancer metabolomics is an area of growing interest. A recent study was able to determine a differential metabolic signature based on BRCA1 functionality [58] and may provide future biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer metabolomics is an area of growing interest. A recent study was able to determine a differential metabolic signature based on BRCA1 functionality [58] and may provide future biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the data from these highresolution methods provides a powerful platform for translational and clinical research and diagnostic applications. 10,11 Targeted metabolomic analysis determines concentrations of a limited and predefined subset of a few metabolites or pathway, whereas untargeted analyses is a global approach. 12 has significant effect on TNBC invasion.…”
Section: Cancer and Metabolomic Profilingmentioning
confidence: 99%
“…20,21 TNBC has similarity with BRCA1 mutation-associated tumors, metabolic profiling of TNBC and hereditary breast and ovarian cancer using non-targeted liquid chromatography coupled to mass spectrometry technology analysis revealed that differential BRCA1 functionality may be used as differential metabolic signature BRCA1-like biomarkers for TNBC and HBOC syndrome. 10,22 Metabolomics studies have revealed that TNBC expresses high and glutathione peroxidase (GPx), glutathione, reducing equivalents (NADPH), and transcription factor Nrf2. 25 Elevated expression of ROS is associated with cancers due deregulated metabolic activity, loss of mitochondria and peroxisome activity, activation of an oncogene, and increased expression of oxidases, cyclooxygenases, lipoxygenases, and thymidine phosphorylase.…”
Section: Cancer and Metabolomic Profilingmentioning
confidence: 99%
See 2 more Smart Citations